Teachers' Perceptions in the Development of Student Worksheets (LKPD) Based On Discovery Learning To Improve System Thinking Ability - Eka Candra Kurniawati; Tri Jalmo; Dewi Lengkana (Budapest International Research and Critics University, 2022)
The.purpose of this study is to analyse and explain the Development ofBased Student Worksheets Discovery Learning- to Improve System Thinking Skills for Junior High School Students. The method used is a descriptive method. The sample of this study includes one hundred and ten junior high school teachers from 90 different schools. The data was collected using a questionnaire, while the data analysis technique used proportions. The results showed that the Development of Student Worksheets (Lkpd) Based on Discovery Learning to Improve the System Thinking Ability of Junior High School Students. The teacher does not yet know the very high category system thinking ability, The existing worksheets have not trained students' ability to think systems and are also included in the low category because teachers have not assessed students' ability to think critically. It can be concluded that (Lkpd) Based on Discovery Learning To Improve System Thinking Ability is needed by teachers and students to Improve System Thinking Ability of Junior High School Students.